Optimasi Penerapan Green Supply Chain Management Menggunakan POM-QM For Windows Dalam Meminimalkan Limbah Produksi Batik Royyan Tuban - Cabase, Daniar Casta; Dermawan, Rizky; Mandasari, Virginia (Gorontalo State University, 2026)
This research aims to optimize Green Supply Chain Management (GSCM) implementation in production waste management at Batik Royyan Tuban by integrating the Economic Order Quantity (EOQ) method based on POM-QM for Windows software. The research method used is a case study with a mixed approach: descriptive and quantitative analysis. Data were collected through observations, interviews, and primary and secondary documentation. The results show that the application of EOQ with an annual demand of 19,800 units results in an optimal order quantity of 890 units per order with a total annual inventory cost of Rp 2,224,860. This strategy reduces ordering frequency, optimizes storage space, reduces raw material waste, and supports energy efficiency and carbon emission reduction. The integration of EOQ and GSCM has significantly impacted operational efficiency and environmental sustainability in the batik industry sector.